2022
DOI: 10.30521/jes.1055935
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and computational studies on the optimal positions of NACA airfoils used in horizontal axis wind turbine blades

Abstract: This paper presents a theoretical and computational study to determine the optimal positions of airfoils along the length of the horizontal axis wind turbine blade. We used four and five-digit NACA airfoils to model a 54-meter blade. The lift, drag coefficient, and lift-to-drag ratio of each airfoil are determined by using QBlade software. The aerodynamic performance of the airfoils is studied based on the blade element momentum theory, and Matlab software is used for numerical implementation. The velocity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These results were also found in another study [25]. Both studies [24,25] support the data obtained in the presented study. In addition, NACA4415 airfoil type can achieve higher lift coefficient than NACA0009.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results were also found in another study [25]. Both studies [24,25] support the data obtained in the presented study. In addition, NACA4415 airfoil type can achieve higher lift coefficient than NACA0009.…”
Section: Resultssupporting
confidence: 92%
“…This study [23] confirms the data obtained for NACA0009 airfoil in present study. In a study, NACA4415 lift and drag coefficients were calculated at various angles of attack and they found that the increase for the angle of attack from 0 degrees to 8 degrees increased the lift and drag coefficients [24]. These results were also found in another study [25].…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations